Androgen Regulates Follicle-Stimulating Hormone β Gene Expression in an Activin-Dependent Manner in Immortalized Gonadotropes - SPADY, THOMAS J. (2003)
Little is known about the molecular mechanisms of androgen regulation of the FSHβ gene; however, studies suggest that it consists of a complex feedback loop that involves multiple mechanisms acting at both the level of the hypothalamus and the pituitary. In the present study, we address androgen regulation of the FSHβ gene in immortalized gonadotrope cells and investigate the roles of activin and GnRH in androgen action. Using transient transfection assays in the FSHβ-expressing mouse gonadotrope cell line, LβT2, we demonstrate that androgens stimulate expression of an ovine FSHβ reporter gene in a dose-dependent manner. Mutation of either of two conserved androgen response elements at −245/−231 and −153/−139 within the proximal region of the ovine FSHβ gene promoter abolishes this stimulation, and androgen receptor binds directly to the −244 ARE in vitro. Androgen induction of the FSHβ reporter gene is also dependent upon the activin autocrine loop present in the LβT2 cells, as well as an activin-response element at −138/−124 of the FSHβ gene. However, activin regulation of other genes remains unaffected by androgens. In addition, androgens stimulate expression of a mouse GnRH receptor reporter gene, and thus may indirectly augment the response of the FSHβ gene to GnRH. Taken together, these data demonstrate that, in mouse gonadotropes, androgens act directly on the ovine FSHβ gene to stimulate expression by a mechanism that is dependent upon activin, as well as acting indirectly, potentially through a second mechanism that may be dependent upon induction of GnRH receptor.